PEMBUATAN ASAM OKSALAT DARI SEKAM PADI DENGAN HIDROLISIS BERKATALISATOR NaOH DAN Ca(OH)2 - Mardina, Primata; -, Norhayani; Triutami, Dessy (Jurnal Bahan Alam Terbarukan, 2013)
Rice husk is a major by-product of the rice milling industries. Rice husk  is one of the most common  lignocellulosic materials those can be converted to oxalic acid by alkaline hydrolysis. This research investigated the effect of  the alkaline catalysts at specified temperature and reaction time on the efficiency of  process and  yield of oxalic acid. Oxalic acid was produced by four processes; alkaline hydrolysis, precipitation, acidification, and crystalization. Washed and dryed rice husk was crushed  to obtain 0.25 mm diameterl particles. The main process was performed by dissolving and hydrolyzing 125 grams of rice husk in 500 mL of 3.5 N NaOH and Ca(OH)2. Rice husk, which hydrolyzed by NaOH, was  precipated with CaCl2 before acidification, whereas rice husk, which hydrolyzed by Ca(OH)2 directly acidified by sulphuric acid without precipitation process. Furthermore, water in acidified solution was evaporated to obtain crystal of oxalic acid. The result showed the alkaline catalyst Ca(OH)2 was more eficient than NaOH for hydrolysis. It omitted precipitation process. The highest yield of oxalic acid which produced by Ca(OH)2 catalyzed hydrolysis was 2.232%  at 60oC for 60 minutes.